Worldwide Tinnitus Research: A Bibliometric Analysis of the Published Literature Between 2001 and 2020 - Zhou, Fangwei; Zhang, Tian; Jin, Ying; Ma, Yifei; Xian, Zhipeng; Zeng, Mengting; Yu, Guodong (Frontiers in Neurology, 2022)
Background In recent years, tinnitus has attracted increasing research interest. However, bibliometric analysis of global research on tinnitus is rare. The objective of this study was to identify and describe the foci and developing trends of tinnitus research using a bibliometric approach. Methods Publications related to tinnitus published from 2001 to 2020 were searched for in the Science Citation Index-Expanded (SCI-E) and Social Sciences Citation Index (SSCI) databases in the Web of Science Core Collection of Clarivate Analytics. The bibliometric approach was used to estimate the searched data, and VOSviewer and CiteSpace software were used to identify and analyze research foci and trends in the field of tinnitus. Results A total of 5,748 articles were included. The number of publications on tinnitus has increased dramatically in the last 20 years, especially since 2010. The leading country in terms of publications and access to collaborative networks was the United States. High-frequency keywords included tinnitus, hearing loss, prevalence, management, depression, mechanism, vertigo, hearing, inferior colliculus, and noise. The analyses of keyword burst detection indicated that prevalence, anxiety, and neural network are emerging research hotspots. Conclusion In the past 20 years, academic understanding of tinnitus has improved considerably. This study provides an objective, systematic, and comprehensive analysis of tinnitus-related literature. Furthermore, current hot spots and prospective trends in the field of tinnitus were identified. These results will assist otolaryngologists and audiologists in identifying the evolving dynamics of tinnitus research and highlight areas for prospective research.